Managing and preserving the estates of a deceased's person: the extent of personal representatives' powers and liabilities in Malaysia - Halim, Akmal Hidayah; Mohd Noor , Nor Azlina (AENSI Publisher, 2014)
A personal representative is a fiduciary put in charge of administering the estate of a deceased’s person. The personal representative must at the utmost act with the highest degree of trustworthiness and good faith to ensure that the estate is administered accordingly. As the personal representative steps into the dead man’s shoes, he is vested with some powers to enable him to manage and preserve the estate. Nevertheless, one question that has nagged the office of personal representative is that what should be the extent of his liabilities for any losses resulting from actions taken in the course of exercising his powers. Hence, this paper seeks to examine the powers vested in a personal representative and to identify the extent of the personal representative’s liabilities in dealing with the deceased’s estate. For this purpose, the discussion focuses to analyze relevant statutory provisions as provided by the Probate and Administration Act 1959. An analysis of the decided cases is also made to determine the rights of the personal representative in the exercise of his powers and the available remedy to the legal heirs in cases of mismanagement or negligence on part of the personal representative. The paper predicates that as the personal representative holds a fiduciary duty to ensure that the estate is administered accordingly, he needs to conform to the fiduciary duties and standard of conduct, failing which would result in personal liability or legal action instituted against him by the legal heirs or other interested parties.